The Effect of Social Environment on Household Consumption Patterns through Lifestyle - Kholis, Nur; Salsabila, Fira Talitha (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study examines the influence of the social environment on household consumption patterns through lifestyle. The research sample was 100 employees of PT. Japfa Comfeed Indonesia Gedangan Unit, Sidoarjo Regency. Data were collected using questionnaires distributed directly to workers and analyzed using descriptive analysis, linear regression, and the Sobel test. The study's results include: first, the social environment affects household consumption patterns (the higher a person's social environment, the higher the consumption pattern) and lifestyle (people who live in a high social environment tend to have a more elevated lifestyle). Second, lifestyle directly affects household consumption patterns (people with a high lifestyle will have higher daily consumption) and mediates the influence of the social environment on household consumption (people with an elevated lifestyle and living in a high social environment will have higher daily consumption